The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11999-013-2928-4
|View full text |Cite|
|
Sign up to set email alerts
|

Periarticular Injection in Knee Arthroplasty Improves Quadriceps Function

Abstract: Background The postoperative analgesic potential of periarticular anesthetic infiltration (PAI) after TKA is unclear as are the complications of continuous femoral nerve block on quadriceps function. Questions/purposes We asked (1) whether PAI provides equal or improved postoperative pain control in comparison to a femoral nerve block in patients who have undergone TKA; and (2) if so, whether PAI improves early postoperative quadriceps control and facilitates rehabilitation. Methods We randomized 60 patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
0
6

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 26 publications
11
94
0
6
Order By: Relevance
“…However, patients receiving the PAI also had higher narcotic consumption on the day of surgery, which is unlikely to be the result of the anesthesiologist bias to give narcotics in this group, but rather a result of true increased narcotic demand in this group of patients. The increased narcotic use on the day of surgery found in our study is in distinction to that of other authors [9,34]. Like with the pain scores in their study, Chaumeron et al [9] found lower narcotic consumption in the first 8 hours postoperatively but no difference thereafter.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…However, patients receiving the PAI also had higher narcotic consumption on the day of surgery, which is unlikely to be the result of the anesthesiologist bias to give narcotics in this group, but rather a result of true increased narcotic demand in this group of patients. The increased narcotic use on the day of surgery found in our study is in distinction to that of other authors [9,34]. Like with the pain scores in their study, Chaumeron et al [9] found lower narcotic consumption in the first 8 hours postoperatively but no difference thereafter.…”
Section: Discussionsupporting
confidence: 52%
“…Although no other study used the same pain management protocols, similar studies comparing periarticular injection with nerve blocks showed results close to our study. In a recent clinical trial, Chaumeron et al [9] used a single-strength periarticular injection, which was redosed through an intraarticular catheter on postoperative day 1 and compared this with an indwelling femoral nerve catheter (no sciatic block) used for 48 to 72 hours. This study found lower pain scores for the first 8 hours after surgery in the periarticular injection group and no difference thereafter [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations